The Pan-African Society of Cardiology (PASCAR) in 2013 and beyond - Dzudie, Anastase (Clinics Cardive Publishing, 2013)
ABSTRACT: The biennial Congress of the Pan-African Society of Cardiology (PASCAR) was held in Dakar from 16 to 19 May 2013 under the patronage of his Excellency, Macky Sall, president of the Republic of Senegal. This meeting was remarkable in the diversity of its 700 participants from English-, French- and Portuguese-speaking Africa. Important aspects of cardiovascular disease in Africa were presented in 195 abstracts and numerous talks; the topics were hypertension, obesity, diabetes, heart failure, cardiomyopathies, coronary heart disease, stroke and rheumatic heart disease. The general assembly meeting was marked by the review and adoption of a new constitution and elections of a new PASCAR governing council that will be in office for the next four years. The new leadership of PASCAR has committed itself to strengthening the administrative infrastructure of the organisation, developing programmes to address education and training needs of African cardiovascular practitioners, developing a pan-African multi-national research platform, and ensuring that ministries of health implement national programmes for the prevention and control of cardiovascular and other non-communicable diseases.